Analysis of Movements During the Day - Yakubova Guyokhan (Genius Journals, 2022)
It has been proven that even if the routine is perfectly structured and useful and economical time is not achieved, the student will give in to unexpected desires and wishes due to the change of his emotions. The only way to get rid of useless games, inappropriate shows, and aimless spending of time is to be able to feel physical and mental pleasure, feast of muscles, and"taste" after training through physical activities - exercises, games, competitions. This, in turn, is related to the level of physical culture of physical culture specialists, parents, adults, siblings themselves in a healthy lifestyle (STT). Only a conscious attitude, purposeful actions and the analysis of their effect pave the way for active actions
Keywords: Movements; physical development